2019
DOI: 10.1021/acs.energyfuels.9b02784
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution and Formation Mechanisms of Caking Components of Modified Lignite in Subcritical H2O–CO Systems

Abstract: A new method for the alkali catalytic modification of lignite in subcritical H2O–CO systems is presented, which can greatly improve its caking properties (caking index, >90). Soxhlet extraction technology coupled with GPC (gel permeation chromatography), FTIR (Fourier transform infrared spectroscopy), and 13C-NMR (carbon-13 nuclear magnetic resonance) analysis methods were used to investigate the structural evolution and formation mechanisms of solutes of n-hexane, benzene, and tetrahydrofuran in modified coal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Previous research found that the solutes of Soxhlet extraction were the major caking components in modified coal. 33 Hence, modified coals were separated by Soxhlet extraction, and the extractible solutes were analyzed by 1 H NMR. As shown in Figure 5, the yield of each extractible solute in the modified coals was improved compared with that in raw coal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research found that the solutes of Soxhlet extraction were the major caking components in modified coal. 33 Hence, modified coals were separated by Soxhlet extraction, and the extractible solutes were analyzed by 1 H NMR. As shown in Figure 5, the yield of each extractible solute in the modified coals was improved compared with that in raw coal.…”
Section: Resultsmentioning
confidence: 99%
“…This is also one of the main reasons for the improvement in the the caking index of M 6 . 3,33 Figure 6 presents the 1 H NMR spectra of extractible constituents in raw coal and modified coal with/without the FeS catalyst. For all of the curves, aliphatic hydrogens H al (6.0−0.5 ppm) were dominant, whereas the aromatic hydrogens H ar (9.0−6.0 ppm) were weak, indicating that the hydrogen in extractible constituents was mainly associated with the aliphatic carbons or substituents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the S D value of BS-D and TS-D should also increase. However, previous work showed that BS-D and TS-D both contained polycyclic aromatic structures as their main structures and were attached with substituents such as monocyclic aromatic structures, aliphatic side chains, and oxygen-containing functional groups . Therefore, they undergo polycondensation reactions and produce small molecular byproducts with low aromaticities .…”
Section: Resultsmentioning
confidence: 99%
“…In the stage of 120–150 min, TS-D and BS-D continue to undergo polycondensation reactions and produce small-molecular byproducts with deuterium . Therefore, the deuterium content in NS-D continues to increase and the deuterium content in TS-D gradually decreases.…”
Section: Resultsmentioning
confidence: 99%